Model Terjemah Para Reformist Dalam Buku “Quran: A Reformist Translation” - Nabawiyah, Habsatun; Kamaludin, Kamaludin (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2022)
In today's modern era, the interpretation of the Qur'an has undergone a significant development. Many branches of science are used by Islamic scholars to express the meanings contained in the Qur'an. On the other hand, scholars outside Islam are also interested in interpreting the Qur'an as a guide to science and human life. These orientalist scholars expressed much of their thoughts in understanding the Qur'an. In this paper will be discussed the interpretation of the Qur'an written by Edip Yuksel and friends, in his work entitled "Quran: a Reformist Translation" Yuksel offers a new method of understanding the Qur'an which is considered a new form of reading of the Qur'an that is different from the interpretations of previous Islamic scholars.